2014
DOI: 10.1177/1040638714538020
|View full text |Cite
|
Sign up to set email alerts
|

Outbreak of Bluetongue virus serotype 4 in dairy sheep in Rio de Janeiro, Brazil

Abstract: Abstract. In late January 2013, 10 nonpregnant Lacaune dairy ewes raised under extensive husbandry management on a farm in Rio de Janeiro, Brazil, presented with the general clinical signs of lethargy, hyporexia, edema of the face, hyperemia of the exposed parts of the skin, mouth lesions, pyrexia, and lameness. Additionally, 2 pregnant ewes died suddenly after the onset of respiratory signs. The complete blood counts and biochemistry analyses showed neutrophilic leukocytosis with monocytosis and reactive lymp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
17
0
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 10 publications
3
17
0
4
Order By: Relevance
“…Clinical anaemia had rarely been reported as associated with the disease. In the past, only Balaro et al (2014) have reported this finding in cases of the disease caused by serotype 4 of the virus. In fact, Dercksen and Lewis (2007) have described that absence of anaemia can be used diagnostically for clinical differentiation of bluetongue from other diseases manifested with oedema in the head, e.g., H. contortus or F. hepatica infections.…”
Section: Discussionmentioning
confidence: 85%
“…Clinical anaemia had rarely been reported as associated with the disease. In the past, only Balaro et al (2014) have reported this finding in cases of the disease caused by serotype 4 of the virus. In fact, Dercksen and Lewis (2007) have described that absence of anaemia can be used diagnostically for clinical differentiation of bluetongue from other diseases manifested with oedema in the head, e.g., H. contortus or F. hepatica infections.…”
Section: Discussionmentioning
confidence: 85%
“…In 2011 and 2013, recurrent outbreaks of BT were reported in sheep in the State of Rio de Janeiro, where BTV‐4 serotype was identified (Balaro et al . ,b). In this study, specific antibodies against BTV‐1, 4 and 17 were detected.…”
Section: Discussionmentioning
confidence: 99%
“…In the Americas, BTV‐4 was first reported from a quarantine station in Florida, USA, from Zebu cattle imported from Brazil in 1980 (Groocock & Campbell, ). Later, this serotype was isolated from Puerto Rico and the Dominican Republic in 1990, from Argentina in 1999‐2010 and from Brazil in 2014 (Balaro et al., ; Lager et al., ; Legisa, Gonzalez, De Stefano, Pereda, & Dus Santos, ; Legisa, Gonzalez, & Dus Santos, ; Mo et al., ). Serological survey of Central and South American countries also indicated the prevalence of antibodies against this serotype in some of the countries (Trinidad and Tobago, Barbados, Puerto Rico, Dominican Republic, Argentina, Brazil) in this region (Thompson, Mo, Oviedo, & Homan, ).…”
Section: Discussionmentioning
confidence: 99%
“…Puerto Rico and the Dominican Republic in 1990, from Argentina in 1999-2010and from Brazil in 2014(Balaro et al, 2014Lager et al, 2004;Legisa, Gonzalez, De Stefano, Pereda, & Dus Santos, 2013;Legisa, Gonzalez, & Dus Santos, 2014;Mo et al, 1994). Serological survey of Central and South American countries also indicated the prevalence of antibodies against this serotype in some of the countries (Trinidad and Tobago, Barbados, Puerto Rico, Dominican…”
Section: Primer Designationmentioning
confidence: 99%